الشكوى من المرأة في شعر الأحوص الأنصاري (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
الشكوى إظهار ما يكابده المرء من ألم نفسي, أو جسدي ناتج عن الظلم, والقهر, وسيطرة قوى خارجة عن إرادته ما يقف أمامه عاجزاً لا يستطيع له رداً. و قد حظيت الشكوى من المرأة بنصيب وافر من شعر الأحوص, ولا يمكن أن نفسر ذلك إلا بكون المرأة قد تجاوزت عنده المدلول الجنسي إلى مدلولات أكثر عمقاً, وأهمية, فقد أضحت رمزاً للحلم بكل ما يعنيه لدى  الرجل من قوة وامتداد, وترسيخ وجود . إن الأنوثة في لا وعيه تمثل الحياة, والجنة, والهدى, والفضيلة, والراحة, والسكينة, ولذلك عاملها لغوياً معاملة الأنثى . هذه المعاني الأنثوية النبيلة تعلل كثرة الشكوى من المرأة في شعر الأحوص الذي سعى وراء المرأة . لقد عكس شعره عالم المدينة التي انتعش فيها الغناء والطرب, بما فيه من إيقاع راقص, والشكوى من نساء اشتهرن بالغناء كجميلة, والذلفاء, وسلامة, وغيرهن, وقد فاضت أبياته بالدموع,و رددت الصحراء أصداء استغاثته مما يعاني من الغرام, والسقام, والحرمان . وغير ذلك من المشاعر التي تلمسناها في أشعار الحب العفيف ما يدفعنا إلى التشكيك في انتماء الأحوص إلى الاتجاه العمري . Complaint, in general, is one’s showing of psychological or physical pain caused by oppression, suppression or dominance of irresistible external forces where one stands helpless unable to drive back. The issue of complaint of women repulsion in the poetry of Alahwas is quite predominant. In fact, this cannot be clearly understood unless we come to know what a female, as he conceived her, was far more than a sexual symbol; she definitely meant something much deeper than that, and far more significant. A woman became in Alahwas ‘mind a token of ambition in its strength, extension and existence. Femininity, in Alahwas’ subconscious, represents life, paradise, guidance, virtue, relief and tranquility. It was dealt with, linguistically speaking, in the same way as a female was dealt with. These noble feminine considerations explain the excessive complaint of women repulsion in the poetry of Alahwas who spent much time pursing women. In fact, Alahwas’s poetry reflected urban life where singing, amusement and rhythmical dancing flourished. That urban life, was also full of complaint of women repulsion, those women like Jameela, Zalfaa, Salma and others who were famous singers. Alahwas ’poetic lines were soaked with tears; and the desert itself reiterated the echoes of his love, sickness and rejection and other numerous and painful feelings that are quite common in Platonic love poetry. Therefore, we tend to be dubious that Alahwas belongs to Omar Ibin Abi Rabeea’s trend.